CONTOURS OF EARLY INDIAN YOGA: A COMPARATIVE INQUIRY INTO VEDIC AND JAIN TRADITIONS - Gulgulia, Aarti; Pandey, Shruti Kant (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The origins and development of Yoga in early Indian civilization represent a dynamic confluence of ritual, philosophy, and soteriological inquiry. This paper undertakes a rigorous comparative analysis of two foundational streams of Indian spiritual praxis: the Vedic and the Jain traditions. Challenging the dominant historiographical narrative that centers Yoga solely within the Vedic or Pātañjala framework, the study foregrounds Jainism as a parallel and autonomous system of yogic thought and practice. Through a critical reading of key Jain texts such as Tattvārthasūtra, Samayasāra, Jñānārṇava, and Yogabindu, alongside core Vedic and Upaniṣadic references, the paper reveals how Jain yoga emphasizes ahiṃsā, karma-theory, kāyotsarga, and progressive detachment as the basis of a lifelong meditative discipline. The study also traces continuities and divergences across shared ascetic ideals within the broader Śramaṇa movement and the Upaniṣadic internalization of Vedic ritual. Furthermore, it maps the historical evolution of Jain yogic thought through its classical codifications and contemporary revivals like Prekṣā Dhyāna, Bhāvana Yoga, and Arham Yoga. By integrating textual exegesis, historical reconstruction, and doctrinal comparison, this paper offers a nuanced, pluralistic account of early Indian Yoga, positioning Jainism as not merely complementary to, but critically constitutive of, the subcontinent’s yogic legacy.